Ceftobiprole Compared With Vancomycin Plus Aztreonam in the Treatment of Acute Bacterial Skin and Skin Structure Infections: Results of a Phase 3, Randomized, Double-blind Trial (TARGET). (8th September 2020) - Overcash, J Scott; Kim, Charles; Keech, Richard; Gumenchuk, Illia; Ninov, Borislav; Gonzalez-Rojas, Yaneicy; Waters, Michael; Simeonov, Simeon; Engelhardt, Marc; Saulay, Mikael; Ionescu, Daniel; Smart, Jennifer I; et al.
Abstract: Background: The development of novel broad-spectrum antibiotics, with efficacy against both gram-positive and gram-negative bacteria, has the potential to enhance treatment options for acute bacterial skin and skin structure infections (ABSSSIs). Ceftobiprole is an advanced-generation intravenous cephalosporin with broad in vitro activity against gram-positive (including methicillin-resistant Staphylococcus aureus ) and gram-negative pathogens. Methods: TARGET was a randomized, double-blind, active-controlled, parallel-group, multicenter, phase 3 noninferiority study that compared ceftobiprole with vancomycin plus aztreonam. The Food and Drug Administration-defined primary efficacy endpoint was early clinical response 48–72 hours after treatment initiation in the intent-to-treat (ITT) population and the European Medicines Agency-defined primary endpoint was investigator-assessed clinical success at the test-of-cure (TOC) visit. Noninferiority was defined as the lower limit of the 95% CI for the difference in success rates (ceftobiprole minus vancomycin/aztreonam) >−10%. Safety was assessed through adverse event and laboratory data collection. Results: In total, 679 patients were randomized to ceftobiprole (n = 335) or vancomycin/aztreonam (n = 344). Early clinical success rates were 91.3% and 88.1% in the ceftobiprole and vancomycin/aztreonam groups, respectively, and noninferiority was demonstrated (adjusted difference: 3.3%; 95% CI: −1.2, 7.8). Investigator-assessed clinical success at the TOC visit was similar between the 2 groups, and noninferiority was demonstrated for both the ITT (90.1% vs 89.0%) and clinically evaluable (97.9% vs 95.2%) populations. Both treatment groups displayed similar microbiological success and safety profiles. Conclusions: TARGET demonstrated that ceftobiprole is noninferior to vancomycin/aztreonam in the treatment of ABSSSIs, in terms of early clinical response and investigator-assessed clinical success at the TOC visit. Clinical Trials Registration: NCT03137173. Abstract : TARGET, a randomized, double-blind, active-controlled, multicenter, phase 3 study, demonstrated noninferiority of ceftobiprole to vancomycin/aztreonam in the treatment of acute bacterial skin and skin structure infections, in terms of early clinical response and investigator-assessed clinical success at the test-of-cure visit.